Pengaruh Metode Pembelajaran Kooperatif Team Assisted of Individualitation Terhadap Hasil Belajar Sejarah di SMANegeri I Karawang - Ikina Sabililah Nurillah (Program Studi Pendidikan Sejarah Pascasarjana UNJ, 2016)
This study based on learning of history that it less appealing to students seen on first observations, such as : The first, when a teacher to explain the lesson just some students who really pay attention. Second, looks a lack of interest students against a history lesson, so that the activitiy in the learning process be less active. Third, students less understand the subject matter quite a lot with time to learn that brief so needed a method of learning that can turn on the students in the history of learning. The aim of the study is to reveal the impact of instructional method cooperative learning Team Assisted Individualization against the results of learning history in SMAN 1 Karawang. This study conducted of month August untill months September 2013. The approach research is a quantitative approach with the experiment.